Progress and perspective of the cathode/electrolyte interface construction in all‐solid‐state lithium batteries. Issue 6 (22nd July 2021) - Su, Shiming; Ma, Jiabin; Zhao, Liang; Lin, Kui; Li, Qidong; Lv, Shasha; Kang, Feiyu; He, Yan‐Bing
Abstract: Security risks of flammability and explosion represent major problems with the use of conventional lithium rechargeable batteries using a liquid electrolyte. The application of solid‐state electrolytes could effectively help to avoid these safety concerns. However, integrating the solid‐state electrolytes into the all‐solid‐state lithium batteries is still a huge challenge mainly due to the high interfacial resistance present in the entire battery, especially at the interface between the cathode and the solid‐state electrolyte pellet and the interfaces inside the cathode. Herein, recent progress made from investigations of cathode/solid‐state electrolyte interfacial behaviors including the contact problem, the interlayer diffusion issue, the space‐charge layer effect, and electrochemical compatibility is presented according to the classification of oxide‐, sulfide‐, and polymer‐based solid‐state electrolytes. We also propose strategies for the construction of ideal next‐generation cathode/solid‐state electrolyte interfaces with high room‐temperature ionic conductivity, stable interfacial contact during long cycling, free formation of the space‐charge region, and good compatibility with high‐voltage cathodes. Abstract : In this review, we present the state‐of‐the‐art development in terms of the cathode/solid‐state electrolyte interfacial issues and the corresponding solutions both at the cathode/solid‐state electrolyte pellet interface and inside the cathode. We summarize the major problems affecting the cathode/solid‐state electrolyte interfacial property (poor point‐to‐point solid–solid contact and harmful interfacial reactions) along with progressive solution strategies in terms of different solid‐state electrolyte types (oxide, sulfide, and polymer solid‐state electrolyte). We also outline the investigations of the mechanism underlying the cathode/solid‐state electrolyte interfacial behavior through modeling and advanced characterization methods.